Adjective Clause Errors Corrections in the Writing Using Dulay's Surface Strategy Taxonomy-Analysis (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this research was to investigate common mistakes made by students at Government Urdu mediumschool in Cuddapha while constructing adjective clauses. The goals of this research were to classify the types of mistakes made by students and identify the most often committed errors. Written texts were analyzed descriptively qualitatively to provide data for this research. In this analysis, Dulay's Surface Strategy Taxonomy was used to classify instances of incorrect usage of the relative pronouns who, whose, which, and whose. Forty-five students were recruited at random for this research. Misordering was shown to be the most prevalent kind of mistake made by the pupils, followed by addition, misformation, and omission. Teachers' responsibilities in light of students' slip-ups are analyzed.